ANALISIS KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN SABU RAIJUA TAHUN 2017 - 2019 - Melda Mariana Poeh; Yeriyanto M. Djami; Daniel M. D. U.; Mychael Gatriser Pae (P3M- Politeknik Negeri Kupang, 2021)
The purpose of this study was to determine the financial performance of Sabu Raijua Regency in financial ratios, namely, the ratio of financial independence, the ratio of effectiveness and efficiency, the ratio of harmony and the ratio of growth. In this study the research method used descriptive quantitative research, namely processing the data obtained in the field to provide an analysis of regional financial performance. The place of research was carried out at the Regional Finance Agency of Sabu Raijua Regency. Sources of data used were secondary data sources. Data collection techniques used interviews and documentation. As the data analysis technique, the writer applied performance analysis by measuring the financial ratios of the local government of the Sabu Raijua Regency. Based on the research results, it can be concluded that the financial performance of Sabu Raijua Regency from the calculation of financial ratios was still not good because of the low value of the independence ratio, so it still depends on assistance from the centre. The effectiveness of regional spending was quite good, although the efficiency ratio was still very low. There was no stability between operating expenditure and capital expenditure from the compatibility ratio, so it was not good. The regional growth ratio still has a very low growth rate every year, so it is expected that there will be positive growth every year.